Nusantara Science and Technology Proceedings 2021
DOI: 10.11594/nstp.2021.1307
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Capital Buffer in Sharia Commercial Banks in Indonesia

Abstract: Capital buffer serves to anticipate the risk of unexpected banking systemic risks. Capital buffer is derived from the difference between banks' capital adequacy ratio (CAR)and the minimum capital adequacy ratio (minimum CAR) regulated by policymakers. This research is made to know what factors affect capital buffer in Indonesia Islamic Commercial banks. These factors include Return On Equity (ROE), Non-Performing Finance (NPF), Financing to Deposit Ratio (FDR), and Gross Domestic Product (GDPG). This study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The Financial Services Authority (FSA) regulates bank capital with a minimum requirement of 8%, so that banks have strong capital, because bank capital serves as a reserve to cover bank losses. Widyakto & Wahyudi (2021) and Kryeziu & Hoxha (2021) found a positive effect of CAR on profitability. On the other hand, Purwasih & Wibowo (2021) and Durguti, Krasniqi, & Krasniqi, (2020) found that CAR had a negative effect on profitability, while Sudarsono, Afriadi, & Suciningtias (2021) actually found CAR and profitability has no effect.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Financial Services Authority (FSA) regulates bank capital with a minimum requirement of 8%, so that banks have strong capital, because bank capital serves as a reserve to cover bank losses. Widyakto & Wahyudi (2021) and Kryeziu & Hoxha (2021) found a positive effect of CAR on profitability. On the other hand, Purwasih & Wibowo (2021) and Durguti, Krasniqi, & Krasniqi, (2020) found that CAR had a negative effect on profitability, while Sudarsono, Afriadi, & Suciningtias (2021) actually found CAR and profitability has no effect.…”
Section: Introductionmentioning
confidence: 95%
“…Bank efficiency will determine bank profitability, because bank efficiency is measured by operating expense to operating income ratio (OEIR), namely the ratio between operating costs and operating income, so that if OEIR is high, it indicates that the bank is increasingly inefficient, because operating costs are high (Hossain & Khalid, 2018). Bank management must be able to reduce operating costs so that banks are able to increase their profitability (Widyakto & Wahyudi, 2021). Javaid & Alalawi (2018;Al-Harbi (2019;Istan &Fahlevi (2020, andSetiawan (2021) found a negative effect between OEIR on profitability.…”
Section: Efficiency and Profitabilitymentioning
confidence: 99%